THE EFFECT OF CHATTING AND SMART GAMES HEALTH EDUCATION PACKAGES TOWARD HEALTHY DATING KNOWLEDGE IN ADOLESCENT DURING COVID 19 PANDEMIC - Ida Arimurti Sanjiwani; I Gusti Ayu Pramitaresthi (Jurnal Keperawatan Respati Yogyakarta, 2022)
The Covid-19 pandemic is a global disaster that has an impact on every aspect of life as well as in adolescent. In adolescence is also starting to know dating. Healthy dating is very important especially during pandemic. The aim of this study was to identify chatting and smart games health education packages toward healthy dating knowledge in adolescent during covid19 pandemic. This study used a quasi-experimental research design with one group pre-test and post-test design. 60 samples were chosen by simple random sampling. The results show that there the application of this package can increase of adolescent knowledge of healthy dating (p= 0,001). Chatting and Smart Games Health Education Packages is recommended to be used in Adolescent during pandemic.